Vitamania [compact disc, unabridged] : our obsessive quest for nutritional perfection - Price, Catherine, 1978- (Blackstone Audio, Inc., 2015)
Grounded in history but firmly oriented toward the future, this audio book reveals the surprising story of how our embrace of vitamins led to today's Wild West of dietary supplements and investigates the complicated psychological relationship that developed with these thirteen mysterious chemicals. In so doing, this audio book both demolishes many of our society's most cherished myths about nutrition and challenges listeners to reevaluate our own beliefs.